Encourage work motivation and work discipline towards employee performance - Nur Fitri, Syifa; Aullora, Putri; Firdaus, Mohamad; Haryadi, Didit (International Journal of Applied Finance and Business Studies, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 41 respondents drawn into a sample using non-probability sampling, the saturated sampling / total sampling method—and data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by work motivation; the higher the work motivation, the higher the employee performance. The second hypothesis states that work discipline does not affect employee performance. The third hypothesis is that employee performance is influenced by work motivation and work discipline, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the c ontext of human resource management.